'Forcing a sparse minor' — CORRIGENDUM. (2nd June 2015) - REED, BRUCE; WOOD, DAVID R.
Abstract : The authors would like to rectify a mistake made on the second page, line 50 of their article. The text below explains the changes required. The constant 0.628 on line 50 of page 2 should be 0.638.